Impact of Armed Conflict on Cancer Care in Sudan: Challenges and Strategic Responses - Yasar Ahmed; Nabeeha Karadawi; Mutasim Abubaker; Awad Mustafa (JCO Global Oncology)
The armed conflict that erupted in Sudan on April 15, 2023, has precipitated a catastrophic collapse of the nation's health care system, with oncology services bearing particularly devastating consequences. Once a regional leader in cancer care, Sudan's health care infrastructure, including its flagship Khartoum Oncology Hospital and numerous comprehensive cancer centers, has been rendered nearly nonfunctional. This crisis has left thousands of patients with cancer without access to essential treatments, exacerbating an already dire public health situation. The conflict has not only disrupted medical supply chains but also displaced health care personnel, further crippling the ability to deliver life-saving care. This manuscript provides a critical analysis of the impact of the conflict on cancer care in Sudan, focusing on the redistribution of patients to peripheral oncology centers and the strain on these facilities. Although existing literature has highlighted the collapse of health care infrastructure, this study offers new quantitative data on the surge in patient numbers at centers such as the East Oncology Centre and the White Nile Cancer Centre, alongside the critical shortages of medical supplies. It also underscores the equity concerns arising from the lack of global attention to Sudan's cancer care crisis compared with other conflict zones. By shedding light on these issues, this study aims to galvanize international action to support Sudanese patients with cancer and rebuild its health care system.